Find a Physician by Matching Medical Needs described in your Own Words - Bäumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela (The 6th International Conference on Emerging Ubiquitous Systems and Pervasive Networks (EUSPN 2015) / The 5th International Conference on Current and Future Trends of Information and Communication Technologies in Healthcare (ICTH-2015) / Affiliated Workshops)
The individual search for information about physicians on Web 2.0 platforms can affect almost all aspects of our lives. People can directly access physician rating websites via web browsers or use any search engine to find physician reviews and ratings filtered by location resp. specialty. However, sometimes keyword search does not meet user needs because of the disagreement of users’ common terms queries for symptoms and the widespread medical terminology. In this paper, we present the prototype of a specialised search engine that overcomes this by indexing user-generated content (i.e., review texts) for physician discovery and provides automatic suggestions as well as an appropriate visualisation. On the one hand, we consider the available numeric physician ratings as sorting criterion for the ranking of query results. Furthermore, we extended existing ranking algorithms with respect to domain-specific types and physicians ratings on the other hand. We gathered more than 860,000 review texts and collected more than 213,000 physician records. A random test shows that about 19.7% of 5,100 different words in total are health- related and partly belong to consumer health vocabularies. Our evaluation results show that the query results fit user's particular health issues when seeking for physicians.
Keywords: Physician Discovery; Consumer Health Vocabulary; Common Terms Query

A System for Uncovering Latent Connectivity of Health Care Providers in Online Reviews - Bäumer, Frederik Simon; Geierhos, Michaela; Schulze, Sabine (Information and Software Technologies. 21st International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015. Proceedings)
The contacts a health care provider (HCP), like a physician, has to other HCPs is perceived as a quality characteristic by patients. So far, only the German physician rating website jameda.de gives information about the interconnectedness of HCPs in business networks. However, this network has to be maintained manually and is thus incomplete. We therefore developed a system for uncovering latent connectivity of HCPs in online reviews to provide users with more valuable information about their HCPs. The overall goal of this approach is to extend already existing business networks of HCPs by integrating connections that are newly discovered by our system. Our most recent evaluation results are promising: 70.8 % of the connections extracted from the reviews texts were correctly identified and in total 3,788 relations were recognized that have not been displayed in jameda.de’s network before.
Keywords: Latent Connectivity; Person Named Entity Recognition and Disambiguation; Health Care Provider Reviews

Understanding the Patient 2.0: Gaining Insight into Patients' Rating Behavior by User-generated Physician Review Mining - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context. 9th International and Interdisciplinary Conference, CONTEXT 2015, Lanarca, Cyprus, November 2-6, 2015. Proceedings)
Patients 2.0 increasingly inform themselves about the quality of medical services on physician rating websites. However, little is known about whether the reviews and ratings on these websites truly reflect the quality of services or whether the ratings on these websites are rather influenced by patients’ individual rating behavior. Therefore, we investigate more than 790,000 physician reviews on Germany’s most used physician rating website jameda.de. Our results show that patients’ ratings do not only reflect treatment quality but are also influenced by treatment quality independent factors like age and complaint behavior. Hence, we provide evidence that users should be well aware of user specific rating distortions when intending to make their physician choice based on these ratings.
Keywords: Health 2.0; Rating Behavior; Patient Opinion Mining on Physician Rating Websites

Vom Systemmodell zu disziplinspezifischen Modellen und zurück - Schmitz, Joachim; Fockel, Markus (Tag des Systems Engineering 2015)
Zukünftige mechatronische Systeme entwickeln sich mehr und mehr zu intelligenten technischen Systemen, die durch eine zunehmende Verzahnung der mechanischen, elektrischen und informationsverarbeitenden Anteile gekennzeichnet sind. Um das Zusammenspiel der Disziplinen besser zu beherrschen, werden zunehmend Methoden und disziplinübergreifende Systemmodelle des Systems Engineering genutzt. Offene Probleme sind dabei noch die Nachverfolgbarkeit der Entwicklung (Traceability) und die Verwaltung zueinander konsistenter Versionen von disziplinübergreifenden und disziplinspezifischen Modellen. Dieser Beitrag adressiert diese Probleme durch die Verknüpfung der Spezifikationstechnik CONSENS für den Systementwurf mit dem Datenmanagementwerkzeug SYNECT. Der Beitrag stellt die Konzipierung und prototypische Werkzeugunterstützung für die Verknüpfung von Systemmodellen und disziplinspezifischen MATLAB/Simulink-Modellen vor.

Systementwurf unter Einbeziehung funktionaler Sicherheit bei automobilen Steuergeräten - Meyer, Jan; Fockel, Markus; Holtmann, Jörg (Tag des Systems Engineering 2015)
Automobile Steuergeräte realisieren mehr und mehr sicherheitskritische Funktionen. Nicht erst durch die Einführung der ISO 26262 werden an die Entwicklung sicherheitskritischer Funktionen besondere Anforderungen zum Beispiel in Form von Sicherheitsanalysen gestellt. In der Praxis hat sich herausgestellt, dass durch den bisherigen Systementwurf nicht alle notwendigen Daten für die Sicherheitsanalysen vorlagen. Von daher war eine Erweiterung des bisherigen Vorgehens erforderlich, sodass die benötigten Daten zu den erforderlichen Zeitpunkten vorliegen und die Sicherheitsanalysen ohne aufwendige Nacharbeiten erstellt werden können. Dieser Artikel beschreibt die durchgeführten Erweiterungen und die Erfahrungen, die in Serienprojekten eines automobilen Zulieferers gesammelt wurden.

ReqPat: Efficient Documentation of High-quality Requirements using Controlled Natural Language - Fockel, Markus; Holtmann, Jörg (Proc. of the 23rd International Requirements Engineering Conference 2015 (RE15))
The growing complexity of today's software intensive systems results in an increased size of requirements specifications, which are typically documented by means of natural language (NL). Large NL requirements specifications are prone to contain defects (e.g., contradictions), and the inherent ambiguity of NL impedes automatic techniques to support the requirements engineer. In order to cope with this problem, we conceived a requirements documentation approach implemented in the tool ReqPat. Using a controlled NL, it supports an efficient requirements documentation, an automatic requirements validation, and an automatic transition to models--while still keeping the requirements understandable for all stakeholders.

Model-Driven Allocation Engineering - Pohlmann, Uwe; Hüwe, Marcus (Conference: 30th IEEE/ACM International Conference on Automated Software Engineering (ASE 2015))
Cyber-physical systems (CPSs) provide sophisticated functionality and are controlled by networked electronic control units (ECUs). Nowadays, software engineers use component-based development approaches to develop their software. Moreover, software components have to be allocated to an ECU to be executed. Engineers have to cope with topology-, software-, and timing-dependencies and memory-, scheduling-, and routing-constraints. Currently, engineers use linear programs to specify allocation constraints and to derive a feasible allocation automatically. However, encoding the allocation problem as a linear program is a complex and error-prone task. This paper contributes a model-driven, OCL-based allocation engineering approach for reducing the engineering effort and to avoid failures. We validate our approach with an automotive case study modeled with MechatronicUML. Our validation shows that we can specify allocation constraints with less engineering effort and are able to derive feasible allocations automatically.

Seminar Theses of the Project Group Cybertron - Schäfer, Wilhelm; Dziwok, Stefan; Pohlmann, Uwe; Bobolz, Jan; Czech, Mike; Dann, Andreas Peter; Geismann, Johannes; Hüwe, Marcus; Krieger, Arthur; Piskachev, Goran; Schubert, David; Wohlrab, Rebekka

Debugging Models in the Context of Automotive Software Development - Stockmann, Lars (Proceedings of the Doctoral Symposium of the ACM/IEEE 18th International Conference on Model Driven Engineering Languages and Systems)

Photon Temporal Modes: A Complete Framework for Quantum Information Science - Brecht, Benjamin; Reddy, Dileep V.; Silberhorn, Christine; Raymer, M. G. (Physical Review X)

Direct generation of genuine single-longitudinal-mode narrowband photon pairs - Luo, Kai-Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine (New Journal of Physics)

Scalability, Elasticity, and Efficiency in Cloud Computing - Lehrig, Sebastian; Eikerling, Hendrik; Becker, Steffen (Proceedings of the 11th International ACM SIGSOFT Conference on Quality of Software Architectures)

Analyzing Cost-Efficiency of Cloud Computing Applications with SimuLizar - Lehrig, Sebastian; Eikerling, Hendrik

Disentangling the Role of Contract Types and Sector Disparities for Public Service Motivation - Grund, Christian; Thommes, Kirsten
The intention of "doing good for society" is regarded to be a crucial motivator for employees in the public sector in order for them to perform well. Recent research in the public sector literature calls for a deeper understanding of how this specific public service motivation (PSM) is shaped. In our paper, we analyze how different degrees of inclusion in the public sector impact PSM. We also investigate how prospects of employment relations (fixed-term versus permanent contracts), temporal differences (part-time versus full-time employment), and actual jobs (core versus subsidiary jobs) moderate PSM in public service. Our findings show that aspects of PSM are affected by these employment characteristics in various ways, suggesting that the factors influencing PSM are multifaceted and that actual employment conditions have to be taken into consideration when assessing PSM.

Cooperation in Diverse Teams: The Role of Temporary Group Membership - Grund, Christian; Harbring, Christine; Thommes, Kirsten
In organizations, some team members are assigned to a team for a predefined short period of time, e.g., as they have a temporary contract, while others are permanent members of the same team. In a laboratory experiment we analyze the cooperation levels resulting from diverse teams, where some team members remain with a team and others are switching teams. Our results reveal that teams consisting partly of members with temporary membership display a lower productivity compared to teams of permanent team members only. First, temporary team members cooperate less than permanent team members. Second, individual effort decisions increase with the number of team mates who are of the same type. This second effect holds for both temps and permanents. We argue that social identity is affected by team composition and the individuals' role in a team.

Investigation of parameters for the numerical simulation of self-pierce-riveted joints under crash load - Hein, David; Meschut, Gerson; Hahn, Ortwin (METEC and 2nd ESTAD)

Charakterisierung und Modellierung von mechanischen Fügeverbindungen mit einseitiger Zugänglichkeit für den profilintensiven Leichtbau unter Crashbelastung - Hein, David; Giese, Patrick; Meschut, Gerson; Gumbsch, Peter; Sommer, Silke; Bier, Matthias

Daten- und prognosebasierte Generierung von Modellparametern für die Crashsimulation mechanisch gefügter Verbindungen - Hein, David; Giese, Patrick; Meschut, Gerson; Gumbsch, Peter; Sommer, Silke; Bier, Matthias; Iwainsky, Alfred; Herfert, Daniel; Günther, Matthias (5. Fügetechnisches Gemeinschaftskolloquium)

Anbindung des Virtuellen Prototypen an die Partialmodelle intelligenter technischer Systeme - Berssenbrügge, Jan; Wiederkehr, Olga; Jähn, Claudius; Fischer, Matthias (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Automatische Ableitung geometrischer Eigenschaften von Bauteilen aus dem 3-D-Polygonmodell - Jähn, Claudius; Fischer, Matthias; Gerges, Maria; Berssenbrügge, Jan (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)